Chong Jia Xin receives Pro-Chancellor Award - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 5 November 2022 – A mechanic’s daughter, Chong Jia Xin, 25, who is a graduate of the Bachelor of Electronics Engineering Technology (Computer System) with Honours was selected as the recipient of the Pro-Chancellor Award at the Universiti Malaysia Pahang (UMP) 17th Convocation Ceremony.